2017
DOI: 10.1097/mao.0000000000001451
|View full text |Cite
|
Sign up to set email alerts
|

Pain After Cochlear Implantation: An Unusual Complication?

Abstract: Pain in the implanted area can be a major complication leading to implant non-use. Rate may be underestimated because of the lack of medical report. At explantation, we recommend systematic evaluation of biofilm and device failure regardless of the suspected etiology of the pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 21 publications
3
27
0
Order By: Relevance
“…Bacteria rapidly form a biofilm on the surface of the foreign body, and bacteria in biofilm can be difficult to eradicate with antibiotic treatment as they multiply slowly and are protected against antibiotics due to enhanced antibiotic tolerance and resistance [19][20][21]. The formation of biofilm may be an explanation for the small increase in the incidence of prolonged postoperative pain found in our study as an association between biofilm and pain has also been demonstrated by others evaluating prolonged pain after temporary or permanent synthetic implant placement [22,23]. However, in actual numbers the incidence with or without antibiotic prophylaxis was low at 0.4% and 0.6%, respectively.…”
Section: Discussionsupporting
confidence: 73%
“…Bacteria rapidly form a biofilm on the surface of the foreign body, and bacteria in biofilm can be difficult to eradicate with antibiotic treatment as they multiply slowly and are protected against antibiotics due to enhanced antibiotic tolerance and resistance [19][20][21]. The formation of biofilm may be an explanation for the small increase in the incidence of prolonged postoperative pain found in our study as an association between biofilm and pain has also been demonstrated by others evaluating prolonged pain after temporary or permanent synthetic implant placement [22,23]. However, in actual numbers the incidence with or without antibiotic prophylaxis was low at 0.4% and 0.6%, respectively.…”
Section: Discussionsupporting
confidence: 73%
“…Because, the patients with soft failure have non-specific and unproven complaints such as pain, tinnitus or intermittent interruption of signals. In this situation, all of in vivo and ex vivo tests are normal and the only thing that shows that the problem is in the device, replacing the device can correct all complaints [6,27]. In our two cases (patient 1 and 10), we thought soft failure before the revision surgery.…”
Section: Discussionmentioning
confidence: 77%
“…In this regard, transcutaneous ultrasound is a valuable imaging modality that avoids radiation exposure and has been described for the diagnostic workup of haematoma around the CI and for detecting magnet dislocation [16][17][18]. However, the literature on the feasibility and reliability of ultrasound in other CI complications has so far been limited to a few case reports [13,19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Although many studies have focused on the surgical and medical complications that occur after cochlear implantation [4][5][6]10], data on imaging methods for the optimal diagnostic workup of these complications is limited and inconclusive. Mostly, temporal bone computed tomography (CT) or X-ray examination is recommended when dealing with cochlear implant (CI) complications [7,8,[11][12][13][14]. In this context, 82.4% of CT scans showed no abnormalities in CI complications but exposed the patients to radiation [15].…”
Section: Introductionmentioning
confidence: 99%